2005
DOI: 10.1021/bi051160w
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Annexins with the mu Subunits of the Clathrin Assembly Proteins

Abstract: A number of biochemical and genetic studies have suggested that certain annexins play important roles in the endocytic pathway, possibly involving the generation, localization, or fusion of endocytic compartments. In a yeast two-hybrid screen for proteins that interact with the N-terminal domain of annexin A2 we identified the mu2 subunit of the clathrin assembly protein complex AP-2. The interaction depended upon two copies of a YxxΦ amino acid sequence motif (Y ) tyrosine, x ) variable residue, Φ ) bulky, hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…8, A and B). This phosphomimic of Anxa6 reportedly exhibits a conformation resembling the Ca 2ϩ -bound state of WT and is assumed to possess a more flexible, open structure, enabling it to interact with multiple membranes simultaneously (39,40,54). Furthermore, cells stably expressing T356D were found to be superior to WT Anxa6 in defending PE-induced hypertrophy (Fig.…”
Section: Anxa6mentioning
confidence: 96%
See 2 more Smart Citations
“…8, A and B). This phosphomimic of Anxa6 reportedly exhibits a conformation resembling the Ca 2ϩ -bound state of WT and is assumed to possess a more flexible, open structure, enabling it to interact with multiple membranes simultaneously (39,40,54). Furthermore, cells stably expressing T356D were found to be superior to WT Anxa6 in defending PE-induced hypertrophy (Fig.…”
Section: Anxa6mentioning
confidence: 96%
“…6E. ture that can simultaneously bind multiple membranes (39,40). We found that membrane association of Anxa6 T356D under PE treatment was more prominent than that of Anxa6 FL (Fig.…”
Section: D Inset)mentioning
confidence: 99%
See 1 more Smart Citation
“…The targeting of AnxA6 to membrane locations via the phospholipid is regulated by the pH and the levels of cholesterol (12)(13)(14). AnxA6 contributes to membrane organization; participates in cholesterol homeostasis (12,13,15,16); regulates the interactions of membranes and actin during endocytic transport (17,18); and regulates secretory events with S100 proteins (19) and tumor protein D52 (TPD52) (20). The interaction of AnxA6 with activated protein kinase C (PKC)-α and p120GTPase-activating protein (GAP) (21-23) may downregulate the epidermal growth factor receptor (EGFR)/Ras signaling pathway, since p120GAP is the sole GAP known to bind to EGFR and promote the hydrolysis of Ras-GTP (24).…”
Section: Introductionmentioning
confidence: 99%
“…It belongs to the network of membrane-cytoskeleton linkages (ChasserotGolaz et al, 1996) and is also associated to CLATHRIN coated vesicles (Creutz and Snyder, 2005) and to early and late endosomes, where it appears to be involved in intracellular vesicle movement and MVB formation (Merrifield et al, 1999;Mayran et al, 2003).…”
Section: Tissue Distribution and Intracellular Localization Of Annexinsmentioning
confidence: 99%